1998
DOI: 10.4039/ent130703-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate and Forest Structure on Duration of Forest Tent Caterpillar Outbreaks Across Central Ontario, Canada

Abstract: We examined the effect of forest structure and climate on large-scale and long-term patterns of outbreaks of forest tent caterpillar, Malacosoma disstria Hbn., across central Ontario. This was done using previously published data on outbreak duration and forest heterogeneity, combined with high-resolution climatic data simulated by the recently developed Ontario Climate Model. Our analysis, which eliminates some of the spatially confounding effects of forest structure and climate, suggests that both the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…As mentioned above, there is also strong evidence that forest tent caterpillar dynamics are influenced by forestry and land-development practices, with the degree of forest fragmentation being a major determinant of outbreak duration (Roland 1993;Roland et al 1998;Cooke and Roland 2000; but see Wood et al 2010). Roland (2005) also found that populations exhibited more rapid cycles in contiguous than in fragmented forests and concluded that forest structure had a significant impact on the lagged density-dependent processes that drive outbreak cycles, in particular through its effects on natural enemies (Rothman and Roland 1998;Roland 2005).…”
Section: S70mentioning
confidence: 98%
“…As mentioned above, there is also strong evidence that forest tent caterpillar dynamics are influenced by forestry and land-development practices, with the degree of forest fragmentation being a major determinant of outbreak duration (Roland 1993;Roland et al 1998;Cooke and Roland 2000; but see Wood et al 2010). Roland (2005) also found that populations exhibited more rapid cycles in contiguous than in fragmented forests and concluded that forest structure had a significant impact on the lagged density-dependent processes that drive outbreak cycles, in particular through its effects on natural enemies (Rothman and Roland 1998;Roland 2005).…”
Section: S70mentioning
confidence: 98%
“…Although the mean supercooling point of locust eggs is below À20 C, more of them died at temperatures above the supercooling point, indicating the occurrence of pre-freezing mortality. Roland et al (1998) suggested that the frequency of cold temperatures following hatch is a better predictor of the northern limit for forest insect outbreaks. If the locust's northward spread is limited by its maximum supercooling point, the outbreak intensity would probably be determined by survival at low temperature.…”
Section: Survival At Low Temperaturesmentioning
confidence: 99%
“…For newly introduced species, local temperatures and overwintering conditions can determine a species' ability to establish and become invasive (Bale 2002, Paradis et al 2008. Temperature can also determine if an established insect becomes a pest, and outbreaks of insect pests have been related to changing temperature conditions (Bale et al 2002) and overwintering success (Virtanen et al 1996, Roland et al 1998). …”
Section: Introductionmentioning
confidence: 99%